2019
DOI: 10.1136/bmjopen-2018-024974
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an antenatal maternal supplementation with prebiotics for preventing atopic dermatitis in high-risk children (the PREGRALL study): protocol for a randomised controlled trial

Abstract: IntroductionAtopic dermatitis (AD) is a chronic inflammatory disease affecting 10%–15% of children in Europe. There is a need for new primary preventive therapeutic strategies in at-risk populations. Recent research has indicated that atopic diseases are associated with a disrupted gut microbial ‘balance’ in early life raising the possibility that interventions which yield optimal patterns of microflora could improve host’s health. Prebiotics, sugars with immunomodulatory properties that stimulate the diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In one ongoing trial pregnant women and prospective mothers of at-risk offspring are being enrolled and given the prebiotic inulin to determine effects on the occurrence of atopic dermatitis as a primary end point and early predictive readout of allergy. 77 The results of this study are still pending.…”
Section: Solutionsmentioning
confidence: 87%
“…In one ongoing trial pregnant women and prospective mothers of at-risk offspring are being enrolled and given the prebiotic inulin to determine effects on the occurrence of atopic dermatitis as a primary end point and early predictive readout of allergy. 77 The results of this study are still pending.…”
Section: Solutionsmentioning
confidence: 87%
“…SYMBA investigates the effects of maternal prebiotic supplementation from 18–20 weeks gestation during pregnancy until 6 months of lactation on the development of infant allergic disease ( 135 ). PREGRALL aims to evaluate the effectiveness of gestational prebiotic supplementation (from 20th week of gestation until delivery) on the occurrence of AD at 1 year of age in at-risk children ( 136 ). Because lactation is also a crucial period for the implementation of major systems, HMO supplementation of breastfed babies from non-secretor mother could be considered as preventive strategy for non-communicable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Further, murine studies have demonstrated that prebiotic fiber supplementation during pregnancy or lactation reduces risk of atopy in offspring (11,12). Similar trials are currently underway in humans [SYMBA (13) and PREGRALL (14)]. Recently, Lee-Sarwar et al reported higher fecal acetate levels (relative to total SCFA) in pregnant women of children less likely to develop atopic disease (15).…”
Section: Introductionmentioning
confidence: 99%